Pengaruh Model Pembelajaran Discovery Learning Terhadap Penguasaan Konsep Kelas X TITL SMK Negeri 1 Kediri - Sonia Ayuni Widianingrum; Puput Wanarti Rusimamto (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
This study aims to (1) analyze students' understanding of concepts with the discovery learning model and direct learning model, (2) analyze how effectively the discovery learning model is applied to the mastery of the concept of PDE subject class X TITL SMK Negeri 1 Kediri, (3) find out student responses to the discovery learning model on electromechanical basic work subjects. This study was carried out by giving treatment to the experimental class given the treatment that was taught by discovery learning and the comparison class, namely the control class with the direct learning model. This study involved 34 students from class TITL 2 SMKN 1 Kediri. Concept mastery tests, consisting of pretest and posttest, as well as questionnaires, were used in this study to measure students' responses to the use of discovery learning. According to the results of the recapitulation of the Mann Whitney hypothesis test, (1) shows a difference in mastery of the concept obtained a significance with a value of 0.012 <0.05, which means that rejecting H0 and accepting H1. Therefore, it can be said that students who are taught by discovery learning and students who use direct learning have significantly different mastery of concepts. (2) The discovery learning learning model succeeded in mastering students' concepts with an average N-Gain score of 0.80 and high criteria. (3) Students of the discovery learning model in increasing mastery of the concept are included in the high category, getting a score of 80%.